2022
DOI: 10.3389/fvets.2022.973450
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies in pig industry of China: Epidemiology in pigs and practitioner awareness

Abstract: Pseudorabies virus (PRV) is widely prevalent in China, which can transmit from pigs to other mammals. Moreover, a PRV variant isolated from an acute human encephalitis case was documented recently. It is imperative to investigate PRV epidemiology in pigs, the knowledge regarding pseudorabies (PR) and self-protection behaviors upon working among relevant practitioners including pig farmers, pig cutters, and pork salesman. In the present study, 18,812 pig serum samples and 1,634 tissue samples were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Overall, PHEV, PRV, CSFV, and JEV are still popular in many countries around the world, and cause different degrees of damages to the pig industry (5,6,13,14,20,21,28,29,57). In China, some provinces have recently reported the prevalence of PHEV, PRV, CSFV, and JEV (41,47,51,(58)(59)(60)(61)(62)(63)(64)(65). The nasal cavity or throat swabs from 1-to 3-week-old piglets in Jilin province in 2010 showed a positivity rate of 44.23% (207/468) for PHEV (58).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, PHEV, PRV, CSFV, and JEV are still popular in many countries around the world, and cause different degrees of damages to the pig industry (5,6,13,14,20,21,28,29,57). In China, some provinces have recently reported the prevalence of PHEV, PRV, CSFV, and JEV (41,47,51,(58)(59)(60)(61)(62)(63)(64)(65). The nasal cavity or throat swabs from 1-to 3-week-old piglets in Jilin province in 2010 showed a positivity rate of 44.23% (207/468) for PHEV (58).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have indicated that the prevalence of PRV-gE antibodies in pig farms in China has exhibited a gradual increase from 2011 to 2016, followed by a subsequent decline from 2016 to 2021. Notably, the overall positive rate of PRV-gE antibodies has remained at ∼20% over the past 2 years (26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%